Learning via a social media enabled tool: Do learning styles make a difference? - Balakrishnan, Vimala (2014)
This paper investigated if students' varying learning styles affect the use of social media for learning based on two learning styles, that is independent and collaborative. Questionnaires were used to gather the students' perceptions after using a social media enabled tool, which was specifically developed based on three key factors (l.e, Self, Effort and Function). A total of 48 students with Computer Science background were recruited to participate in the experiment. Path modeling analyses indicate the factors to predict 70% and 59% of usage among the independent and collaborative groups, respectively. Results show collaborative students to emphasize more on Function and Effort than Self, whereas Self and Effort had stronger impacts on the independent students than Function. Pair-wise comparisons revealed the differences between the learning styles to be significant for Self and Function, that is Self to be more important for independent students whereas Function Was more important for the collaborative students. No significant differences were noted for Effort. The findings clearly indicate that students' learning styles play important "oles in their learning activities, and hence academics should look into the possibilities of using different approaches in their teaching practices.